Promoting scholarship of engagement using the appreciative inquiry model" The case of Mangosuthu Uiversity of Technology, South Africa - Nkonki-Mandleni, B.; Netshandama, V. O.; Ighodaro, I. D. (South African Journal of Higher Education, 2025)
This article aims to demonstrate how appreciative inquiry (Ai) model was used to promote the scholarship of engagement (SoE) at Mangosuthu University of Technology (MUT) in South Africa. Qualitative research was conducted through group consultative sessions following the Ai model. Data analysis involved interpreting words, phrases, and nonverbal cues from group discussions. Findings included staff recognition of the importance of integrating community engagement (CE) into teaching, learning, and research at MUT. A need was also identified to integrate indigenous knowledge systems (IKS) into CE for better feedback on curricular development. It was suggested that for successful integration of CE into teaching, learning, and research (TL&R), MUT's Executive Management could prioritize CE's importance. While it is early to measure Ai's impact on MUT's transition to SoE, its application facilitated smooth engagement in consultations. Recommendations include promoting understanding and prioritization of CE within the MUT community to align it with TL&R.